Autovaccine-Based Immunotherapy: A Promising Approach for Male Recurrent Urinary Tract Infections - Alexandru Ciudin; Bernat Padulles; Razvan Popescu; Pasqualino Manasia (Life, 2024)
Background: Recurrent Urinary Tract Infections (UTIs) in men range from 0.9 to 2.4/1000 individuals in younger men to 7.7/1000 in those over 85, significantly impacting their quality of life. Preventive strategies include autovaccines, but limited evidence exists for males. Methods: A prospective monocentric, open-label observational study was conducted from August 2018 to August 2021, with follow-up until August 2023 including patients with recurrent UTIs treated with immunotherapy. We evaluated the incidence rate of UTIs per year, the incidence rate of episodes after two or three rounds of the autovaccine, and quality of life measured with the IPSS-QoL questionnaire. Results: A total of 49 patients fulfilled inclusion criteria. The mean age was 72 years (±15), and the median 61. The evolution of UTIs number of episodes after the autovaccine rounds: −37.74% for the first round from 5.3 to 3.3; −33.33% for the second round from 3.3 to 2.2; −45.45% for the third round from 2.2 to 1.2. The mean IPSS score improved from 10.69 to 7.27 after the treatment (32%). The mean QoL subscore enhancement was from 4.22 to 1.92 (54%). With a mean follow-up of 3 years, only nine patients required retreatment. Conclusion: Autovaccine treatment significantly reduced the number of UTI episodes, with a cumulative effect observed after multiple rounds of treatment, demonstrating an enhancement in QoL and with sustained effectiveness and a low need for retreatment.